Efeitos da compressão isquêmica na catastrofização da dor em indivíduos com cervicalgia crônica: um estudo quase experimental - (:unkn) unknown (UNIFAP – Universidade Federal do Amapá)
Chronic neck pain is a common disorder in the general population, where the myofascial component stands out as the main cause, affecting mainly the trapezius muscle, where there is the presence of myofascial trigger points (MTPs). MTPs are painful hypersensitive nodules located in a band of muscle tension that can be latent or active. The prolonged painful impulses caused by these MTPs can cause the phenomenon of central sensitization, which are structural changes in the central nervous system. These changes are related to poor emotional and cognitive adaptation as well as pain catastrophizing and other psychosocial factors. There are several effective physiotherapeutic techniques for the management of neck pain, including ischemic compression, which is a manual therapy technique widely used with the aim of inactivating MTPs. AIM: to evaluate the effects of ischemic compression on the outcome of pain catastrophizing in individuals with chronic neck pain. MATERIAL AND METHODS: this is a quasi-experimental study. Eleven individuals of both sexes, aged between 18 and 60 years with chronic neck pain, Neck Disability Index score ≥ 5 and central bilateral active trigger point in the trapezius muscle, were included in the study. Participants received 5 sessions of ischemic compression, with pre-intervention, post-intervention assessment 24 hours after the last session and post-intervention assessment 1 week after the last session. The instruments used to measure the variables pain catastrophizing, pain intensity and pressure pain threshold were the catastrophic thoughts about pain scale (EPCD), numerical pain scale (END) and algometry using the INSTRUTERM® PTR- 300 respectively. RESULTS: the NRS score at pre, post 24h and 1 week was 6.45(±2.16), 2.36(±1.80) and 1.36(±1.91), respectively. As for EPCD, the values were 2.66(±0.76) in the pre-intervention, 0.68(±0.69) in the 24h post and 0.44(±0.39) in the 1 week post. Algometry found the right PPT with the following scores: 1.27(±0.46) before, 1.80(±0.80) after 24 hours and 1.70(±0.61) after 1 week. In the left PPT, the values were: 1.12(±0.40), 1.68(±0.85) and remained at 1.68(±0.73) in the pre, post 24h and 1 week periods, respectively. CONCLUSION: The study demonstrated that five sessions of IC resulted in significant improvements in pain catastrophizing, pain intensity and increased pressure pain threshold in people with chronic neck pain of myofascial source.
Keywords: Cervicalgia - Terapia manual; Cervicalgia crônica - Distúrbio; Dor crônica - Fisioterapia; Compressão isquêmica; CNPQ::CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL